Factors Associated with In-stent Restenosis in Patients Following Percutaneous Coronary Intervention - Dedi Wihanda; Idrus Alwi; Hamzah Shatri; E. Mudjaddid E. Mudjaddid (Acta Medica Indonesiana, 2015)
Aim: to determine factors associated with In-Stent Restenosis (ISR) in patients following Percutaneous Coronary Intervention (PCI). Methods: a retrospective cross-sectional study was conducted using secondary information from medical records of post-PCI patients who underwent follow-up of angiography PCI between January 2009 and March 2014 at The Integrated Cardiovascular Service Unit, Cipto Mangunkusumo Hospital, Jakarta. Angiographic ISR was defined when the diameter of stenosis ≥50% at follow-up angiography including the diameter inside the stent and diameter with five-mm protrusion out of the proximal and distal ends of the stent. Results: there were 289 subjects including 133 subjects with and 156 subjects without ISR. The incidence of ISR in patients using of bare-metal stent (BMS) and drug-eluting stent (DES) were 61.3% and 40.7%, respectively. Factors associated with ISR are stent-type (OR=4.83, 95% CI 2.51-9.30), stent length (OR=3.71, 95% CI 1.99-6.90), bifurcation lesions (OR=2.43, 95% CI 1.16-5.10), smoking (OR=2.30, 95% CI 1.33-3.99), vascular diameter (OR=2.18, 95% CI 1.2-3.73), hypertension (OR=2.16, 95% CI 1.16-4.04) and diabetes mellitus (OR=2.14, 95% CI 1.23-3.70). Conclusion: stent type, stent length, bifurcation lesions, smoking, vascular diameter, hypertension and DM are factors associated with ISR in patients following PCI.